In Defence of Our Humanity - Hill, Stephen. author. aut Link
XII, 368 p. 1 illus.
Keywords: This book is based on Stephen Hill’s direct experience working in the United Nations for many years as consultant and over a decade as full time Member of Staff—based in Indonesia and part-time in Paris, serving as United Nations Regional Director for Science for Asia and the Pacific as well as Principal Director and Ambassador of the United Nations Agency UNESCO (the UN Educational, Scientific, and Cultural Organization) across South East Asia. It was not always a quiet life. Stephen had to handle the negotiations and aftermath of two of his own UN staff taken hostage in 1996 for five months by freedom fighters into the jungles of West Papua; the May 1998 Revolution in Indonesia where he had to escape his house at 2.00am through mobs and fires while his own security staff had changed into civilian clothes and run off down the street to escape, then evacuate everyone else, but stay to report to the UN Security Council and liaise with the incoming Transition Government. In the early 2000s, Stephen needed to escape Indonesia, under UN Security instruction, from the terrorist organisation, Abu Sayyaf from Mindanao, the Southern Philippines, when they sent a Hit Squad down through Manado and across Sulawesi towards Jakarta to assassinate him in Jakarta because of his collaborative work throughout Mindanao’s previous fundamentalist Islamic conflict zones, amongst other things, bringing literacy to 7,000 villagers, mainly women, building nine radio stations with community support across religious lines, and introducing basic education into Islamic Schools previously teaching only the Koran and Arabic. This book captures all of this rather exciting life but delivers a message from experience—the Power of Community and Cultural Empowerment in successful United Nations Action to bring positive change into the world.